Efficacy and safety of first-line or second-line selective laser trabeculoplasty for normal-tension glaucoma: a multicentre cohort study - Tomoko Naito; Kazuyuki Hirooka; Toru Nakazawa; Masaki Tanito; Shiro Mizoue; Katsuyoshi Suzuki; Keiji Yoshikawa; Itaru Kimura; Yasushi Ikuno; Takako Miki; Kazuhisa Sugiyama; Tairo Kimura; et al. (BMJ Open Ophthalmology)
Background/aims This study aimed to investigate and compare the efficacy and safety of first-line and second-line selective laser trabeculoplasty (SLT) in Japanese patients with normal-tension glaucoma (NTG).Methods 100 patients with NTG were enrolled in this study. Patients were treated with SLT as a first-line or second-line treatment for NTG. Main outcome measures were intraocular pressure (IOP) reduction rate, outflow pressure improvement rate (ΔOP), success rate at 1 year and complications. Success was defined as ΔOP≥20% (criterion A) or an IOP reduction ≥20% (criterion B) without additional IOP-lowering eye-drops, repeat SLT or additional glaucoma surgeries. The incidence of transient IOP spike (>5 mm Hg from the pretreatment IOP), conjunctival hyperaemia, inflammation in the anterior chamber and visual impairment due to SLT were assessed.Results A total of 99 patients (99 eyes) were initially enrolled in this study, including 74 eyes assigned to the first-line SLT group and 25 eyes to the second-line SLT group. The mean IOP of 16.3±2.1 mm Hg before SLT decreased by 17.1%±9.5% to 13.4±1.9 mm Hg at 12 months after SLT in the first-line group (p<0.001), and the mean IOP of 15.4±1.5 mm Hg before SLT decreased by 12.7%±9.7% to 13.2±2.0 mm Hg at 12 months after SLT (p=0.005) in the second-line group. Both groups showed significant reductions in IOP. Higher pre-SLT IOP and thinner central corneal thickness were associated with greater IOP reduction. The success rate at 1 year was higher in the first-line compared with the second-line group, with lower pretreatment IOP and the use of IOP-lowering medication before SLT being associated with treatment failure. Most post-treatment complications were minor and transient.Conclusions SLT may be an effective and safe treatment option for NTG, as either a first-line or second-line treatment.Trial registration number The study was registered in the UMIN-CTR (UMIN Test ID: UMIN R000044059).